Metallic Implants: Atomic Scale Origin of Metal Ion Release from Hip Implant Taper Junctions (Adv. Sci. 5/2020). Issue 5 (4th March 2020) - Balachandran, Shanoob; Zachariah, Zita; Fischer, Alfons; Mayweg, David; Wimmer, Markus A.; Raabe, Dierk; Herbig, Michael
Abstract : In article 1903008, Shanoob Balachandran, Zita Zachariah, and co‐authors reveal the fretting corrosion mechanisms in a cobalt alloy/titanium alloy taper junction present in modular hip implants. Although the cobalt alloy is more wear resistant than the titanium alloy, microploughing phenomena on the titanium alloy surface promote tribocorrosion in the cobalt alloy, resulting in metal ion release into the body.